The English Language Centre Community College Qatar: A Position Report - Irum Naz (17948078) (2016)
This study provides a comprehensive profile of the English Language Centre (ELC) and its various stakeholders at the Community College of Qatar. It considers the program's relative strengths and weaknesses as well as ways in which it might best be developed in the interests of efficiency, expediency, and improved learning outcomes for students. The study was conducted in the ELC by faculty members and administrators involved in the day-to-day operations of the facility. It involved the collection of qualitative and quantitative data following comprehensive research efforts and preceding rigorous data analysis and interpretation. The focus of the study was the quality of the Foundation Program at CCQ and the manner in which it might be upgraded to provide a better learning experience for students – one that would help them to accelerate through the levels of the program with optimal learning outcomes. With regard to the curriculum, participants felt that the existing program would benefit from significant revisions. These would include narrowing the focus of courses and providing sets of very specific learning objectives for students, with attention to preventing repetition between levels and subjects. The idea of integrating skills was also put forth as a means of increasing the efficiency of the program and rendering it more cost effective. Finally, in terms of assessment, the data suggested that a set of standardized assessments that more closely suited the programs of study should be devised to assess students more fairly and accurately than at present. In terms of student learning outcomes, it was recommended that students undergo a more comprehensive placement process to ensure that they begin the program at an appropriate level and get the maximum benefit from their experience in the ELC. Although this also ties into the idea of curriculum change, it was hoped that students could leave the ELC having had exposure to courses in English for specific purposes (ESP). This would help to enhance learning outcomes for students and make the program more practical in its capacity to provide applied learning experiences for students. Finally, the idea of a more reliable exit assessment for students was raised frequently as a means by which the ELC could regulate itself and ensure optimum learning outcomes for students finishing the program. Finally, with respect to the general learning environment in the ELC, there were a number of important recommendations which participants felt would benefit ELC students greatly. One of these was the provision of a learning center for students that would help them to receive personalized tuition and differentiated instruction. Another was a recommendation that an extra level be added to the ELC to accommodate the different levels of English language proficiency represented among ELC students. Further recommendations were related to class size and length as well as building a stronger relationship with the Transition program to expedite the conversion to that program for students. The study was comprehensive in scope and rigorous in the thoroughness of its data collection and analysis. The evidence collected in the course of conducting the study suggests that significant change is needed in the structure of the ELC program specifically with regard to curriculum, learning outcomes for students, and the ELC‟s learning environment in general. The study also reveals, however, that fairly specific changes and the manner by which these can be implemented are both identifiable and considered attainable by stakeholders in the ELC. That is to say that members of the ELC are confident that meaningful change can be effected and implemented in a timely and expedient manner. With the cooperation of the department and its various stakeholders, the ELC can evolve and grow into an effective unit that maximizes its utility for students and the communities in which they live. Other Information Report prepared by: The English Language Centre (ELC) Curriculum Committee License: http://creativecommons.org/licenses/by/4.0 See the English Language Centre's website: https://www.ccq.edu.qa/English/Academics/ELC/Pages/default.aspx